Referential and Visual Cues to Structural Choice in Visually Situated Sentence Production - Myachykov, Andriy; Thompson, Dominic; Scheepers, Christoph; Garrod, Simon (Frontiers in Psychology, 2012)
We investigated how conceptually informative (referent preview) and conceptually uninformative (pointer to referent’s location) visual cues affect structural choice during English transitive sentence production. Cueing the Agent or the Patient prior to presenting the target event reliably predicted the likelihood of selecting this referent as the sentential Subject, triggering, correspondingly, the choice between active and passive voice. Importantly, there was no difference in the magnitude of the general Cueing effect between the informative and uninformative cueing conditions, suggesting that attentionally driven structural selection relies on a direct automatic mapping mechanism from attentional focus to the Subject’s position in a sentence. This mechanism is, therefore, independent of accessing semantic, and possibly lexical, information about the cued referent provided by referent preview.